Respuestas
Respuesta dada por:
2
Revisa que cumpla una de las siguientes formas:
![{(a + b)}^{2} = {a}^{2} + 2ab + {b}^{2} {(a + b)}^{2} = {a}^{2} + 2ab + {b}^{2}](https://tex.z-dn.net/?f=+%7B%28a+%2B+b%29%7D%5E%7B2%7D++%3D++%7Ba%7D%5E%7B2%7D++%2B+2ab+%2B++%7Bb%7D%5E%7B2%7D+)
![{(a - b)}^{2} = {a}^{2} - 2ab + {b}^{2} {(a - b)}^{2} = {a}^{2} - 2ab + {b}^{2}](https://tex.z-dn.net/?f=%7B%28a++-++b%29%7D%5E%7B2%7D++%3D++%7Ba%7D%5E%7B2%7D+++-+2ab+%2B++%7Bb%7D%5E%7B2%7D+)
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años